Cardiorespiratory fitness and cardiovascular risk among in-patients with depression compared to healthy controls - Gerber, Markus; Cody, Robyn; Beck, Johannes; Brand, Serge; Donath, Lars; Eckert, Anne; Hatzinger, Martin; Imboden, Christian; Kreppke, Jan-Niklas; Lang, Undine E.; Ludyga, Sebastian; Mans, Sarah; et al. (Frontiers in Psychiatry, 2023)
Introduction Compared to the general population, individuals with depression have an increased risk for cardiovascular diseases. Nevertheless, little is known so far whether cardiorespiratory fitness (CRF) moderates this relationship. Therefore, we examined whether common physiological cardiovascular risk factors differ between patients with depression and healthy (non-depressed) controls, whether patients and controls differ in CRF, and whether higher CRF is associated with a lower cardiovascular risk in both patients and healthy controls. Additionally, we examined whether within the patient sample, cardiovascular risk factors differ between patients with mild, moderate and severe depression, and whether the relationship between symptom severity and cardiovascular risk is moderated by patients’ CRF levels. Methods Data from a multi-centric, two-arm randomized controlled trial (RCT) was analyzed, including 210 patients (F32, single episode: n = 72, F33, recurrent major depression: n = 135, F31-II, bipolar type II: n = 3) and 125 healthy controls. Waist circumference, body mass index, body fat, blood pressure, cholesterol levels, triglycerides, and blood glucose were considered as cardiovascular risk markers. CRF was assessed with a submaximal ergometer test. Differences between groups were examined via χ2-tests and (multivariate) analyses of covariance. Results Compared to healthy controls, patients with depression had a higher cardiovascular risk as evident from about half of the examined indicators. In the total sample, participants with good CRF had more favourable scores across nearly all risk markers than counterparts with poor CRF. For most variables, no interaction occurred between group and fitness, indicating that in patients and controls, similar differences existed between participants with poor and good CRF. Few differences in risk markers were found between patients with mild, moderate and severe depression, and no interaction occurred between depression severity and CRF. Discussion Patients with depression and healthy controls differ in several cardiovascular risk markers, putting patients at increased risk for CVDs. In contrast, people with good CRF show more favourable cardiovascular risk scores, a relationship which was observed in both healthy controls and patients with depression. Physical health of psychiatric patients should receive the clinical attention that it deserves. Lifestyle interventions targeting healthy diet and/or physical activity are recommended as a physically active and healthy lifestyle contributes equally to patients’ mental well-being and cardiovascular health.